A Comprehensive Analysis of the Drivers Behind the Effective Tax Rate of Financial Times Stock Exchange (FTSE) in Malaysia - Suzalee Saidin; Nadiah Abd Hamid; Saifulrizan Norizan; Aida Hazlin Ismail (Universitas Pasundan, 2023)
This study examines corporate effective tax rates (ETR) of Malaysian multinational corporations (MNC) listed in the Financial Times Stock Exchange (FTSE) Bursa Malaysia Kuala Lumpur Composite Index (KLCI) and FTSE Bursa Malaysia Mid 70 Index. The main objective of this study is to examine the relationship between the ETR of MNCs with subsidiaries in tax haven countries, and selected corporate characteristics such as firm size, leverage, capital intensity, return on assets, inventory intensity, profit margin, and foreign directors. Using a multiple linear regression approach on a balanced panel sample of 68 companies (321 firm-years) spanning 2017 to 2021, the study provides evidence for the variability of corporate ETRs in which the average corporate ETRs falls below the STR for the financial year 2021 of 24%. The statistical results also reveal that lower ETRs are associated with highly leveraged companies, and greater investments in fixed assets. Further, a negative coefficient for return on assets and profit margin suggests that companies have benefited from tax incentives provided by the government. Hence, this study contributes to tax literature and policymakers on factors that influence the corporate ETR, especially MNC with subsidiaries in tax haven countries. Tax authorities should implement tight monitoring to avoid these MNCs extensively engaging in tax planning which will result in revenue loss to the Malaysian income tax collection.